BIRO JODOH ONLINE: KEGUNAAN DAN DAMPAK - Regita Amelia Cahyani; Rizqa Febry Ayu (JURIS (Jurnal Ilmiah Syariah), 2020)
Along with the development of technology in the digital era, it is increasingly easier to access communication. Various applications used in the process of finding a partner. One of them is the emergence of an online matchmaking application which is experiencing rapid development. So that the transition to the concept of matchmaking from conventional to online is not new, along with the times. This research focuses on the implications for today's online matchmaking agencies. This research used a qualitative approachand using descriptive analytical method. The results showed thatonline matchmaking agencies, although they have positive and negative impacts for their users, but it is not an obstacle for partner seekers through cyberspace.